Pengaruh Efektivitas Penggunaan Power BI terhadap Efisiensi Waktu Audit - Denny Rachmad P.P; Agus Munandar (Universitas Sains dan Teknologi Komputer, 2026)
This study aims to examine the effectiveness of using the Power BI dashboard in monitoring audit progress, as well as its impact on the efficiency of audit completion times. Given their busy schedules and the length of audit procedures, auditors require a tool capable of monitoring each stage of the audit quickly, in a structured manner, and in real time. To address this need, this study employs a qualitative descriptive approach combining a literature review, document analysis, and in-depth interviews with five informants from the internal audit division, with the validity of the findings reinforced through source triangulation. The entire analysis process is framed within the Technology Acceptance Model (TAM) to understand how Business Intelligence technology is accepted and utilised in day-to-day audit monitoring practices. The research findings indicate that the Power BI dashboard is considered easy to learn and operate, thereby fostering a perception of high ease of use and utility. These positive perceptions foster an accepting attitude, generate an intention to continue using the tool, and are reflected in regular, actual usage. The use of the dashboard has been shown to reduce the time taken to ascertain the progress of an audit from around thirty minutes to less than one minute, whilst also reducing the risk of data loss as all information is centralised on a single platform. This study concludes that such efficiency is not solely a function of technology, but rather the result of the interaction between technology, data quality and user discipline.